2017
DOI: 10.1172/jci91211
|View full text |Cite
|
Sign up to set email alerts
|

Targeting PPARγ in the epigenome rescues genetic metabolic defects in mice

Abstract: RES and MAL conceived all studies, with help from DJS and SEM. Most of the experiments were designed by RES and performed by ERC, YHF, and KKB. Additional experiments were conducted by JRD (macrophage and 3T3-L1 ChIP-seq); DJS (H3K27ac and Pol2 ChIP-seq); MJE (cold exposure); MK and PS (primary adipocyte culture); CJM and JFJ (some Ucp1 studies); and ERB, LCP, and RKD (animal husbandry and other assays). Computational analyses of RNA-seq were done by ZL and ChIP-seq by RES, with help from SRR, MD, HWL, and KJW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 86 publications
7
49
0
Order By: Relevance
“…Thus, adipocytes become less capable during onset of obesity in their crucial functions such as lipid storage that indirectly maintain normal hepatocyte and skeletal muscle glucose handling. Recent results exploring effects of HFD in mice on the global DNA site binding and transcriptional activity of PPARγ also show how environmental cues can modulate the epigenome and alter adipocyte function 150 .…”
Section: Cellular and Molecular Causes Of Impaired Insulin Responsivementioning
confidence: 99%
“…Thus, adipocytes become less capable during onset of obesity in their crucial functions such as lipid storage that indirectly maintain normal hepatocyte and skeletal muscle glucose handling. Recent results exploring effects of HFD in mice on the global DNA site binding and transcriptional activity of PPARγ also show how environmental cues can modulate the epigenome and alter adipocyte function 150 .…”
Section: Cellular and Molecular Causes Of Impaired Insulin Responsivementioning
confidence: 99%
“…It may, in turn, durably change the expression of PPARγ target genes. Consistent with this hypothesis, findings have shown that PPARγ down‐regulation in obese mice is associated with a decrease in genome‐wide association occupancy of PPARγ (30).…”
Section: Discussionmentioning
confidence: 67%
“…However, others have also shown that obesity is associated with a decline in the PPARγ2 activity and expression (2933). These modifications seem to be strongly associated with the pathogenesis of the metabolic syndrome (3033). The decrease in PPARγ2 gene expression might be seen as an adaptive mechanism to prevent further fat accumulation in WAT (33).…”
Section: Discussionmentioning
confidence: 99%
“…The associations of impaired scWAT function with effects on energy balance and insulin sensitivity in Rosi-treated Cited4knockout mice are consistent with previous reports demonstrating the key role of subcutaneous fat for the therapeutic action of TZDs. This was evident in humans and rodents both at the level of gene expression and browning and at the level of tissue metabolism (Boden et al, 2005;Bogacka et al, 2005;Festuccia et al, 2009;Soccio et al, 2017). Obesity is associated with reduced capacity or compromised mitochondrial oxidation in adipose tissue and the ability of TZDs to restore these defects is likely to be important for insulin sensitization, possibly through the improvement of systemic lipid metabolism (Wilson-Fritch et al, 2004;Rong et al, 2007;Soccio et al, 2017).…”
Section: Oxygen Consumptionmentioning
confidence: 99%
“…Beyond their ability to enhance adipocyte formation and turnover, TZDs promote mitochondrial biogenesis and fatty acid oxidation in human and rodent white adipose tissue and increase its thermogenic potential ("browning";Okuno et al, 1998;Fukui et al, 2000;Yamauchi et al, 2001;Wilson-Fritch et al, 2004;Boden et al, 2005;Bogacka et al, 2005;Tang et al, 2011). Interestingly, the enrichment of pathways of mitochondrial oxidation and lipid metabolism in subcutaneous fat was recently shown to be the most prominent effect of the TZD rosiglitazone on the transcriptome across adipose tissues (Soccio et al, 2017). Increased capacity for adipose tissue thermogenesis is generally accepted to be protective against insulin resistance and dyslipidemia but to which extent the regulation of browning by TZDs mediates insulin sensitization remains unclear (Sidossis & Kajimura, 2015).…”
Section: Introductionmentioning
confidence: 99%